2021
DOI: 10.1002/btm2.10226
|View full text |Cite
|
Sign up to set email alerts
|

Cell stiffness predicts cancer cell sensitivity to ultrasound as a selective superficial cancer therapy

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…Our results are comparable to those of previous studies on cancer cells. Low-intensity pulsed ultrasound stimulation at 20 kHz of frequency and energies between 2.8 and 6.6 J/ cm 2 also decreased the cell elastic modulus for squamous cells, carcinomas, and melanomas, indicating that cancer cells were less stiff than noncancerous cells [63].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are comparable to those of previous studies on cancer cells. Low-intensity pulsed ultrasound stimulation at 20 kHz of frequency and energies between 2.8 and 6.6 J/ cm 2 also decreased the cell elastic modulus for squamous cells, carcinomas, and melanomas, indicating that cancer cells were less stiff than noncancerous cells [63].…”
Section: Discussionmentioning
confidence: 96%
“…Specifically, Wang et al observed autophagy, apoptosis, and mitochondrial structural and functional damage to cancer cells [70]. Bergman et al also demonstrated that the viability decreased in cancer cells due to a lesser frequency applied in ultrasound (20 kHz) [63].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, particular 65,79 (b) mechanical stretch, 151,152,160 (c) high-intensity ultrasound frequency, 45,75,136,138,139 (d) and low-intensity pulsed ultrasound. 55,68,70,71 . (e) Targeting cells associated with tumor-associated T-cells, 114,119 dendritic cells, 130,132,138 tumor-associated macrophages, 149 and cancer-associated fibroblasts.…”
Section: Extracellular Matrix (Ecm)mentioning
confidence: 99%
“…Schematic representation of mechanobiology-based therapies. Targeting cancer cells by mechanical perturbations like (a) shock wave, , (b) mechanical stretch, ,, (c) high-intensity ultrasound frequency, ,,,, (d) and low-intensity pulsed ultrasound. ,,, . (e) Targeting cells associated with tumor-associated T-cells, , dendritic cells, ,, tumor-associated macrophages, and cancer-associated fibroblasts .…”
Section: Mechanobiological Strategies Targeting the Tumor Microenviro...mentioning
confidence: 99%
See 1 more Smart Citation